Correlations between muscle-tendon parameters and acceleration ability in 20 m sprints - Monte, Andrea (PLoS One, 2019)
In this study we investigated the relationships between muscle-tendon parameters and average/peak values of velocity, force and power in sprint running focusing on the acceleration phase. Eighteen male sprinters (100 m PB: 10.66±0.51 s) participated to the study. Instantaneous values of horizontal velocity (v) were recorded by means of a radar and instantaneous values of force (F) and power (P) were calculated based on these data. Muscle thickness, fascicle length and pennation angle of knee extensors and plantar flexors, as well as Achilles tendon length and CSA, were measured by means of ultrasonography. In the first 20 m of the sprint average and peak speed were 6.31±0.59 and 8.88±0.98 m·s(-1), respectively; force was highest at the start of the sprint (F(peak) = 10.02±1.43 N·kg(-1)) and power peaked about 1 s after the start (26.64±5.99 W·kg(-1)). Muscle-tendon parameters showed stronger correlations with peak values of power (R range: 0.81–0.92), force (R range: 0.56–0.84) and speed (R range: 0.53–0.85) than with average values of velocity over the 20 m distance (R range: 0.41–0.61) (R <0.47 = NS; R >0.71 = P < .001). These data underline that the influence of muscle tendon parameters on sprint performance could be better appreciated when peak values of power can be calculated rather than by considering the simple measure of average velocity (e.g. distance/time).